2020
DOI: 10.3389/fpls.2019.01785
|View full text |Cite
|
Sign up to set email alerts
|

Low Amplitude Boom-and-Bust Cycles Define the Septoria Nodorum Blotch Interaction

Abstract: pattern as a low-amplitude boom-and-bust cycle in contrast with the classical high amplitude boom-and-bust cycles seen for biotrophic pathogens where the contrast between resistance and susceptibility is typically much greater. Implications of the results are discussed relating to breeding strategies for more sustainable SNB resistance and more generally for pathogens with NEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 63 publications
(72 reference statements)
2
41
1
Order By: Relevance
“…While SN15, 15FG114 and WAC13443 harbour SnTox3 haplotype 1, WAC13404 and 16FG168 possess haplotype 5 and 2, respectively (Table 1 , Phan et al . 41 ). The SnTox3 haplotype 1 and 5 encode the same SnTox3 protein isoform I, haplotype 2 encodes SnTox3 isoform II with a 3 aa difference (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While SN15, 15FG114 and WAC13443 harbour SnTox3 haplotype 1, WAC13404 and 16FG168 possess haplotype 5 and 2, respectively (Table 1 , Phan et al . 41 ). The SnTox3 haplotype 1 and 5 encode the same SnTox3 protein isoform I, haplotype 2 encodes SnTox3 isoform II with a 3 aa difference (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To be able to control the disease effectively, information on pathogenicity profiles of the pathogen which exist within a local population is invaluable. Our previous study on Australian P. nodorum population genetic diversity has revealed a five-group structure with contrasting properties 41 . Infection assays indicate that newly emerged isolates were more pathogenic, demonstrating evidence of selection.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although there are a few reports indicating single dominant genes conferring resistance to nodorum blotch (Ma and Hughes, 1995;Murphy et al, 2000), a number of studies have shown that inheritance of resistance is quantitative, involving several minor genes contributing small but additive effects (Aguilar et al, 2005;Friesen and Faris, 2010;Shankar et al, 2008). Resistance is, therefore, mainly partial and may undergo a low-amplitude boom-and-bust cycle in contrast to the classical high amplitude boom-and-bust cycle seen for single major gene resistance to biotrophic diseases (Phan et al, 2020). P. nodorum is heterothallic and ascospores (sexual spores) produced in pseudothecia are the primary source of inoculum (Bathgate and Loughman, 2001;Keller et al, 1997;Solomon et al, 2006).…”
mentioning
confidence: 99%